UNIT 1.27 Spectral Flow Cytometry. Issue 1 (January 2013) - Nolan, John P.; Condello, Danilo
Abstract: Interest in measuring the complete fluorescence spectra of individual cells in flow can be traced to the earliest days of flow cytometry. Recent advances in detectors, optics, and computation have made it possible to make full spectral measurements in the sub‐millisecond time frame in which flow cytometry measurements typically occur. This opens up new possibilities for applying spectroscopy to the analysis of individual cells. This unit reviews historical and contemporary approaches to spectral flow cytometry, as well as instrument design, calibration, and data analysis for spectral flow cytometry applications. Curr. Protoc. Cytom. 63:1.27.1‐1.27.13. © 2013 by John Wiley & Sons, Inc.